2020
DOI: 10.3390/brainsci10060373
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal Full Endoscopic Posterolateral Transforaminal Lumbar Interbody Fusion with Endoscopic Disc Drilling Preparation Technique for Symptomatic Foraminal Stenosis Secondary to Severe Collapsed Disc Space: A Clinical and Computer Tomographic Study with Technical Note

Abstract: Background: Severe collapsed disc secondary to degenerative spinal conditions leads to significant foraminal stenosis. We hypothesized that uniportal posterolateral transforaminal lumbar interbody fusion with endoscopic disc drilling technique could be safely applied to the collapsed disc space to improve patients’ pain score, restore disc height, and correct the segmental angular parameters. Methods: We included patients who met the indication criteria for lumbar fusion and underwent uniportal full endoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…A large autografted titanium 3-dimensional-printed cage can be inserted under regional anesthesia while sedation is monitored safely. In the authors’ experience, having a larger working area allowed placement of a larger interbody cage and hence necessitated an expandable cage [ 95 ]. They demonstrated the technique in the treatment of a patient with grade 2 spondylolisthesis and instability [ 93 ].…”
Section: Interlaminar Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A large autografted titanium 3-dimensional-printed cage can be inserted under regional anesthesia while sedation is monitored safely. In the authors’ experience, having a larger working area allowed placement of a larger interbody cage and hence necessitated an expandable cage [ 95 ]. They demonstrated the technique in the treatment of a patient with grade 2 spondylolisthesis and instability [ 93 ].…”
Section: Interlaminar Approachmentioning
confidence: 99%
“…In the authors' experience, having a larger working area allowed placement of a larger interbody cage and hence necessitated an expandable cage. 95 They demonstrated the technique in the treatment of a patient with grade 2 spondylolisthesis and instability. 93 There is little literature on posterolateral transforaminal endoscopic lumbar interbody fusion.…”
mentioning
confidence: 99%
“…Wenjie Wu compared the application of Endo-TLIF with MIS-TLIF for the treatment of lumbar degenerative disease; they found that Endo-TLIF was effective for patients with single-segment lumbar degenerative diseases, and it was characterized by minor injury, quicker recovery, and lower cost [ 17 ]. Pang Hung Wu revealed that uniportal endoscopic posterolateral lumbar interbody fusion was feasible in the treatment of severe foraminal stenosis secondary to severe collapsed disc space, where the VAS score decreased 4.3 ± 1.0 at the last follow-up, and disc height was restored significantly [ 18 ]. In our study, the VAS score and ODI of the 42 patients decreased from 7.51 ± 1.91 and 82.42 ± 8.7% to 2.09 ± 0.59 and 11.09 ± 3.2%, respectively, and the clinical symptoms improved significantly at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In comparision, the majority of spinal endoscopies are percutaneous posterior procedures with neglible blood loss, minimal muscle dissection, and hardly any postoperative wound pain. These posterior transforaminal or interlaminar decompression procedures seem preferred by most endoscopic spine surgeons for greater versatility, simplicity, and lower risks to the vital structures in the spine [49][50][51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%